Investigation of Performance and Residual Stress Generation of AlSi10Mg Processed by Selective Laser Melting - Lianfeng Wang; Xiaohui Jiang; Yihong Zhu; Zishan Ding; Xiaogang Zhu; Jing Sun; Biao Yan (Advances in Materials Science and Engineering)
During the selective laser melting (SLM) process, the scanned layers are subjected to rapid thermal cycles. By working on the mechanical properties, residual stress, and microstructure, the high-temperature gradients can have significant effect on the proper functioning and the structural integrity of built parts. This work presents a comprehensive study on the scanning path type and preheating temperature for AlSi10Mg alloy during SLM. According to the results, SLM AlSi10Mg parts fabricated in chessboard scanning strategy have higher mechanical properties or at least comparable to the parts fabricated in uniformity scanning strategy. In the SLM processing, the residual stress in different parts of the specimen varies with temperature gradient, and the residual stress at the edge of the specimen is obviously larger than that at the center. Under the chessboard scanning and preheating temperature 160°C, the residual stress in each direction of the specimens reaches the minimum. Under different forming processes, the morphology of the microstructure is obviously different. With the increase of preheating temperature, the molten pool in the side surface is obviously elongated and highly unevenly distributed. From the coupling relationship between the residual stress and microstructure, it can be found that the microstructure of top surface is affected by residual stresses σx and σy. But the side surface is mainly governed by residual stress σy; moreover, the greater the residual stress, the more obvious the grain tilt. In the XY and XZ surfaces, the scanning strategy has little influence on the tilt angle of the grain. But, the tilt angle and morphology of the microstructure are obviously affected by the preheating temperature. The results show that the residual stresses can effectively change the properties of the materials under the combined influence of scanning strategy and preheating temperature.